ANALYSIS OF OIL PALM SUSTAINABLE REPLANTING MODELS, A CASE AT PT. AGROWIYANA , TUNGGUL ULU, TANJUNG JABUNG BARAT, JAMBI - Solikhin Solikhin; Anas M. Fauzi; Hadi K. Purwadaria (Jurnal Manajemen & Agribisnis, 2012)
The oil palm replanting program is becoming of importance for the next decade as some of oil palm plantations are reaching the productivity peak. This research was aimed to select the priority of oil palm replanting strategy with respect to the related factors and impacts to the share holders of PIR Trans and KPPA plantation of PT. AGROWIYANA , and to identify key success indicators of replanting model. A discriptive research methodoligy was carried out using Analytical Hierarchy Process (AHP) and Focus Group Discussion (FGD) involving multi stakeholders of PT. AGROWIYANA . Results of this research indicated that financial is considered as the most important factor for replanting implemention with the total cutting using standard technology as chosen replanting strategy. The funding scheme through intensive fund rising IDAPERTABUN needs to be well prepared to involve more farmer groups.Keywords: PT. AGROWIYANA , Replanting Strategy